The relationship between ownership structure and real earnings management practices: evidence from Malaysian public companies - Muhammad Shaheer Nuhu; Zauwiyah Ahmad; Lim Ying Zhee (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aimed to examine the mitigating effects of ownership structure on real earnings management practices among Malaysian public-listed firms. Data was collected from firms listed on Bursa Malaysia’s main market, covering the years 2011 through 2021. The findings of Generalised Least Squares panel regression confirmed the significant negative effect of family ownership and foreign ownership on listed firms’ real earnings management, while managerial ownership and ownership concentration demonstrated insignificant effects. Practically, this study offers an effective framework for ownership structure and real earnings management practices to reduce executive managers' opportunistic behaviour. The findings contribute to a broader understanding of these phenomena so that investors and other stakeholders can better analyse earnings reports and, therefore, make informed decisions, particularly pertaining to non-owner-controlled firms.